Ueinzz e esquizodrama: notas sobre experiências brasileiras favoráveis a uma ecologia dos afetos - Queiroga, Joaquim Pedro Maciel (2023)
This research is part of the institutional project “Challenges on mental health: sustainability and subjectivity on the contemporary world”, approved by the National Council for Scientific and Technological Development, CNPq (25/2020), included in the UN Agenda 2030 and in the 17 Sustainable Development Goals (SDG), as it assumes the conception that, on the contemporary world, the experience of a sustainable subjectivity implies the adoption of interdisciplinary methods and techniques and, overall, a research and pedagogical approach that aims at a rigorous analysis of the new risks that continuously resets the limits between normal and pathological, subjective and objective, nature and culture. The main objectives of the institutional project aim to: 1. Describe and analyze, systematically and comparatively, the therapeutical principles of different psychoanalytical approaches; 2. Analyze the possibilities of subjective sustainment before the challenges of the contemporary world (among them, a few stand out, like: burnout, borderline, thresholds between art and science, nature and culture, individualism and narcissism, trauma and deterritorialization narratives, vulnerability and loneliness (isolation). As a part of the project, this research pretends, mainly, to investigate the Brazilian reception on schizoanalysis (Deleuze and Guattari), as well as the possible associations with the concept that we propose in this work, that is, the concept of an ecology of affections. For that, we focused on two Brazilian experiences: the schizodramatical approach and Ueinzz Theatrical Company. An ecology of affections proposes to fortify the balance between the limits and possibilities of each individual and the environment that that they live in. It also proposes a space for creativity and creative sharing in different social groups. The challenge to which we are sensible on this work consists in detecting the creation of unconscious regimes that are able, somehow, to resist the psychic weakening that are the result of excluding social norms. It’s important to remember that both the schizoanalysis created by Gilles Deleuze and Félix Guattari and the schizodrama created by Gregório Baremblitt are not contained in a clinical sphere. For them, the notion of “care” is essential, in and out of the therapeutical field. It is known that Brazil receives, until today, not only schizoanalysis, but the whole thinking by that pair of authors as an important contribution for many areas of thought, such as psychology, philosophy and art. We intend, therefore, to explore this fertile soil and investigate its products on the schizoanalytical and theatrical clinics. National Council for Scientific and Technological Development, CNPq (project n.: 130310/2021-2)